Solidarity (In)action? - Lemberg-Pedersen, Martin (Politik, 2011)
This article assesses the claim that the EU secures basic rights for citizens and migrants because externalization facilitates solidarity between EU states, third countries and migrants (the EFS-argument). However, it is argued that practices like European Commission (EC)-donations to UNHCR, the outsourcing to Private Security Companies (PSCs) like Finmeccanica or the subsidising of EUROSUR-projects do not facilitate solidarity. Rather they place the largest responsibility for refugees on the world’s poorest states, and consolidate the criminalization of irregular migration. Furthermore, Dublin-concepts like “safe third countries” (STCs) and “first country of arrival” are criticized for being instrumentalised by Northern European states’ to defect responsibility for migrants. The EU border control has thus developed into a transnational regime that systematically creates border-induced displacement of migrants. Consequently, a critical evaluation of the EFS-argument reveals a grave inconsistency between the EU’s stated value and the consequences of externalization.